"Decoding MH"—A de‐stigmatization campaign in the Hong Kong Police Force. (20th September 2022) - Chan, Elaine Yin Ling; Lui, Jasmine Tsz Ting; Mak, Alison Lai Ping; Lau, Edmond Kam Lun
Abstract: Police officers are under high level of stress given the intense and emergent work nature. If left untreated, their mental wellbeing would be at risk and work performance compromised. However, mental health stigma is common among police officers and is perpetuated by factors like police cultures emphasizing toughness and self‐reliance. In view of this, since 2016, the Hong Kong Police Force had launched a holistic campaign for Force members which was the first among law enforcement organizations in Hong Kong, aiming to reduce stigma, by enhancing mental health knowledge and decreasing negative attitudes and behaviors towards mental health issues. The programme incorporated standardised trainings of the Mental Health First Aid course with examples modified to the local police context, and psychoeducation via the use of digital medium and sharing by public figures. Positive feedback was received. It was foreseen that the campaign effects would increase Force members' awareness of their mental health, encourage help‐seeking and facilitate officers' decision making when encountering crises in the community.